University Social Responsibility, Service Learning, and Students' Personal, Professional, and Civic Education - Coelho, Márcia; Menezes, Isabel (Frontiers in Psychology, 2021)
The long-standing vision of universities as the “alma mater” of students and graduates is a demonstration of its role as sustaining the person, the expert/professional, and the citizen. This role has persisted in the face of rising global challenges such as the emergence of new learning spaces, the growing diversity of publics, the call for productivity and performativity, and the hope for a significant engagement with the community and the public good. These sometimes conflicting tendencies have also stimulated higher education institutions to further pedagogical strategies that articulate in novel ways the classical elements of learning: action/experience and reflection/theory. In this context, service learning received a new impetus, particularly in the post-Bologna European Higher Education Area, as universities were looking for ways in which to articulate the social dimension of HEI and their “third mission” as institutions not only committed to addressing and solving societal problems, but also committed to fostering public-minded alumni through powerful experiences of engagement for both the students and the community. This paper is based on the experience of Erasmus+project ESSA, a service earning based project focused on University social responsibility (USR). ESSA engaged four groups of students from three European universities (Edinburgh, Porto, and Kaunas) in conducting a 1-week on-site USR audit based on an ecologic and situated concept of social responsibility. We will consider the perceived impact of ESSA on 44 students through a thematic analysis of focus group discussions and student self-assessment reports produced during and after their participation in the USR audit.